Is Service with a Smile Enough to Satisfy Customers? Sincere and Insincere Smiles via Video and Vignette - Resekiani Mas Bakar; Fitriani Ayu; Lukman Nadjamuddin (Gadjah Mada International Journal of Business, 2023)
The current service trend does not merely involve face-to-face interactions, including smiling (high-contact-service) by service employees, but also using methods such as texting (low-contact service). Sincere and insincere smile studies have used a method involving dynamic (videos) and static stimuli (photographs). However, research into the different types of smiles is still limited to methods using a vignette. This study aims to examine the effect of the type of smile on customer satisfaction using a vignette and video. A total of 139 people participated in 2 (smile: sincere versus insincere) x 2 (media: vignette versus video) groups. The study found that there is an influence from the type of smile on customer satisfaction. A sincere smile using video produces greater customer satisfaction than using a vignette does, because the emotional contagion process through video is more real than it is through a vignette. The interesting finding from this study is that there is a gap in the insincere smile condition between using video and a vignette. The dissatisfaction of customers is greater when served with an insincere smile by text (vignette), compared with a face-to-face interaction by video. Video could only capture the muscle movement on a person’s cheeks (zygomaticus major), but it could not see the muscle wrinkles formed around the eyes (orbicularis oculi), compared to a vignette. This study implies that although the standard operational procedure (SOP) for service demands friendliness, a customer can feel whether a server’s smile is genuine or fake. The customer’s dissatisfaction toward an insincere smile will be higher with a low-contact service using text than a high-contact service with video.